KESIAPAN GURU TERHADAP IMPLEMENTASI KMBDI SMK NEGERI 1 LUBUK SIKAPING - Fitryya Sherfina; Jonni Mardizal (Unversitas Negeri Padang, 2024)
This independent learning curriculum emphasizes the aspects of independence and courage to learn, and can provide opportunities for teachers to develop learning according to what is needed by students. This study aims to measure the readiness of teachers in the implementation of the Independent Learning Curriculum (KMB) at SMK Negeri 1 Lubuk Sikaping. The method used is a quantitative research with a descriptive approach. The method used was the distribution of questionnaires with a total of 24 statements with 75 respondents. Based on the results of the analysis, the average Respondent Achievement Level (TCR) index in terms of learning planning was 93.87% and in terms of the learning implementation process was 90.45%. Therefore, the readiness of teachers for the implementation of the independent learning curriculum at SMK Negeri 1 Lubuk Sikaping in terms of learning planning and the learning implementation process is categorized as very ready.